Effect of feeding tree foliage on milk yield and composition of lactating goats on semi-arid rangeland - BHATTA, RAGHAVENDRAN; SHINDE, A K; SANKHYAN, S K; VERMA, D; VAITHIYANATHAN, S (The Indian Journal of Animal Sciences, 2014)
Lactating goats (30) of similar milk yield, number of lactation and days in lactation were divided into 2 equal groups. Both the groups were grazed on native range from 08: 00 to 17: 00 hr. First group (G1) was maintained on sole grazing, whereas second group (G2) was fed with tree foliage from Azadirachta indica, Prosopis cineraria and Bauhinia racemosa simultaneously while grazing in range. Dry matter (DM) intake of goat was lower (1364 g/day) in GI than G2 (1585 g/ day). Digestibility of all the major nutrients, except crude protein was significantly (P<0.05) higher in G2 compared to G 1. CP digestibility was 46.8 % in G1 and 22.1 % in G2. Digestible crude protein intake was 46.0 g/day in G1 and significantly (P<0.05) reduced to 23.5 g/day in G2. Metabolizable energy intake was 19.5 and 22.1 MJ/day in G1 and G2 respectively. Feeding of tree foliage increased the milk yield by 58 % in G2 ovcr G1. The milk composition in terms of milk protein and solid-not fat also significantly (P<0.05) improved in G2. It is concluded that feeding of tree foliage in lactating goats maintained on range improved the milk yield and composition.